Performance analysis and power allocation of AF best relay selection in generic noise - Ahmed, Imtiaz; Nasri, Amir; Michalopoulos, Diomidis S.; Schober, Robert; Mallik, Ranjan K. (IEEE Wireless Communications and Networking Conference, WCNC, 2012)
In this paper, we provide a high signal-to-noise ratio (SNR) error rate analysis of amplify-and-forward (AF) best relay selection in networks impaired by Rayleigh fading and generic, possibly non-Gaussian noise. The derived closed - form asymptotic error rate expressions are applicable to any type of noise with finite moments. Exploiting these analytical results, we formulate a power allocation problem with energy consumption fairness constraints for the source and the relays, which is solved using monomial fitting and a series of geometric programs. The accuracy of the derived analytical results and the effectiveness of the proposed power allocation scheme are confirmed with computer simulations. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03